The key criteria that determine the degree to which management's use of competitive intelligence - Ahmed Khalid Alrashedi (Cogent Business & Management, 2023)
This study highlights the critical significance of competitive intelligence (CI) associated to the development of agile management practices within organizations. It is necessary to establish the scheme in order to identify the key characteristics that affect the degree to which management makes use of competitive intelligence. strategic management theory was adopted for this study. A "Decision Making Trial and Evaluation Laboratory" (DEMATEL) method was utilised in order to carry out an investigation into the most significant factors (features) that have an effect on CI. Four different businesses that had effectively implemented competitive intelligence strategies across a variety of business divisions were utilised as case studies in order to gain an understanding of the processes that underlie this new phenomenon. The finding of the research demonstrates that "Strategy Formulation" is the most influential dimension that can determine the degree to which management makes use of competitive intelligence. The study's implication supports the idea that, in today's highly competitive and digital environment, CI strategies require clear conceptualization, and this study focuses on the growing significance of this factor in facilitating the implementation of CI strategies. The results of the study provide more evidence that, in the highly networked and digital world of today, CI strategies are becoming an increasingly vital component for companies to implement through effective strategic formulation.
Keywords: 650; competitive intelligence; competitors' information; information technology; organizational culture; strategic formulation